ANIMATED FILM “NUSSA DAN RARA EPISODE OF FRIENDS TREAT COMPETITION”AS A MEANS FOR PLANTINGEDUCATION IN CHILDREN - Rahmat Hidayat; Husnul Khatimah (Universitas Dharmawangsa, 2020)
Interests will bring shows that do not educate children behind the animated film Nussa and Rara with regard to the ability to appreciate the character of education. This film is one alternative spectacle that can be used for educational inculcation through film. This study aimed to discuss the educational value needed in the animated film Nussa and Rara episode of the Friends Treat Competition through the film. The subject of this research is the animated film Nussa and Rara which are easily taken from the Official Nussa page on youtube. The results of this research are the animated film Nussa and the episodes of the Traktir Ten Competition. The educational values include: curiosity, honesty, success, religious, national spirit, social care and creativity. If children always see shows that educate even those who teach good character and education, then dont deny that in the future the child will become an educated person according to our expectations.